Classification of Types and Factors Violating the Heritage Boundary of Iranian Qanat (Case Study: Qanats of the Eastern Counties of Kerman Province) - Nahid Kamaladini (آب و توسعه پایدار)
The Iranian Qanat Chain Case, which includes 11 prominent Qanats, was added to the World Heritage List in 2016 after meeting two of UNESCO's six criteria. This record confirms the high importance of Qanats in the formation and sustainability of human settlements on the central plateau of Iran. On the other hand, the international obligations arising from UNESCO laws emphasize the necessity of preserving and improving the status of this living heritage. Nevertheless, studies indicate that the condition of Qanats in Iran is becoming increasingly worrying. Violating the Qanats boundary is one of the fundamental problems that threaten the health of the Qanat structure and the amount and quality of their water.  In this descriptive study, which was conducted using a qualitative method and in-depth interview tools, 30 informed individuals in the Bam, Narmashir, Fahraj, Gonbaki, and Rigan regions were surveyed. This region has ancient, numerous, and high-flowing Qanats, but it faces widespread problems caused by violations of the Qanats’ boundary. The research results identified six main factors: insufficient public awareness, limited access to information about the qanats, poor documentation and mapping, lack of appropriate laws, lack of enforcement support for existing laws, and weak local management. These factors have played a significant role in the continued violation of the Qanat boundary in these areas.